MODAL INSAN DAN KEPENDUDUKAN DALAM PEMBANGUNAN NEGARA MENURUT IBN KHALDUN - Joni Tamkin Borhan; Che Zarrina Sa’ari (State Islamic University North Sumatra, 2009)
Abstract: Human Capital and Demography In State Building in theThought of Ibn Khaldun. The career and thought of Ibn Khaldun has been an object of study for quite a long period of time, yet much aspects seem to be unceasinly attracting scholars’ attention. The present article discusses Ibn Khaldun’s view of human resource and its use in state development. The underlying argumentation of Ibn Khaldun’s seems to be the importance of religion as the salient force of development. Any other natural or social forces-like the ashabiyyah and the natural suvival tendencies-by itself cannot be sufficient as the basis of civilized development.Kata Kunci: Ibn Khaldun, modal insani, pembangunan